Pembelajaran STEAM dalam Perspektif Filsafat Matematika - Putri Melinda Rahmawati; Nanda Nur Indah Kamilatur Rosidah; Lutfi Fatma Hilmasari; Titan Zhafira Widya (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The development of 21st-century education demands critical, creative, collaborative, and communicative thinking skills that can be developed through a STEAM approach that integrates science, technology, engineering, art, and mathematics in an interdisciplinary manner. This research aims to examine STEAM learning in a philosophical framework through ontological, epistemological, and axiological perspectives. This research uses a qualitative approach with a type of literature study through content analysis techniques. The results of the study show that from an ontological perspective, the essence of STEAM is a contextual and adaptive interdisciplinary approach in learning. In an epistemological perspective, STEAM knowledge is built through experimentation, collaborative projects, inquiry, and engineering design, thus gaining understanding through experience and reflection. Meanwhile, from an axiological perspective, STEAM improves problem-solving skills, innovation, responsibility, and awareness of the real world in the 21st century. This study has implications for the development of learning design and STEAM curriculum that emphasizes authentic problem-solving, cross-disciplinary integration, and contextual and meaningful construction of mathematical knowledge.